Reported energy intake versus estimated energy requirements of Portuguese adolescents and young adults - Tallon, José Maria; Narciso, Janine; Saavedra, Raquel; Barros, Ana; Silva, António José; Costa, Aldo Matos (Progress in Nutrition, 2020)
Introduction/objective: Predictive equations are commonly used to estimate basal metabolic rate/resting metabolic rate and determine energy requirements, with the Harris-Benedict equation being amongst the most study equations. However, if this formula effectively addresses basal metabolic rate/resting metabolic rate in individuals living in contemporary societies is still unclear. In the present study we compared the energy intake of Portuguese adolescents/young adults with their energy requirements by gender, age and Body Mass Index category. Methods: This was a cross-sectional study that included 287 participants from the 9th to the 12th grade, that recorded their food intake for at least 3 days in an online platform and had complete anthropometric data. The Harris-Benedict equations were used to estimate the energy requirements of adolescents/young adults. Results: Overall energy intake of adolescents/young adults was significantly lower than their requirements (1898.6 kcal versus 2047.1 kcal, p